Monitoring the level of government trust, risk perception and intention of the general public to adopt protective measures during the influenza A (H1N1) pandemic in the Netherlands - Oudhoff Jurriaan; Beaujean Desirée JMA; Timmermans Daniëlle RM; van der Weerd Willemien; van Steenbergen Jim E (BMC, 2011)
Abstract Background During the course of an influenza pandemic, governments know relatively little about the possibly changing influence of government trust, risk perception, and receipt of information on the public's intention to adopt protective measures or on the acceptance of vaccination. This study aims to identify and describe possible changes in and factors associated with public's intentions during the 2009 influenza A (H1N1) pandemic in the Netherlands. Methods Sixteen cross-sectional telephone surveys were conducted (N = 8060) between April - November 2009. From these repeated measurements three consecutive periods were categorized based on crucial events during the influenza A (H1N1) pandemic. Time trends in government trust, risk perception, intention to adopt protective measures, and the acceptance of vaccination were analysed. Factors associated with an intention to adopt protective measures or vaccination were identified. Results Trust in the government was high, but decreased over time. During the course of the pandemic, perceived vulnerability and an intention to adopt protective measures increased. Trust and vulnerability were associated with an intention to adopt protective measures in general only during period one. Higher levels of intention to receive vaccination were associated with increased government trust, fear/worry, and perceived vulnerability. In periods two and three receipt of information was positively associated with an intention to adopt protective measures. Most respondents wanted to receive information about infection prevention from municipal health services, health care providers, and the media. Conclusions The Dutch response to the H1N1 virus was relatively muted. Higher levels of trust in the government, fear/worry, and perceived vulnerability were all positively related to an intention to accept vaccination. Only fear/worry was positively linked to an intention to adopt protective measures during the entire pandemic. Risk and crisis communication by the government should focus on building and maintaining trust by providing information about preventing infection in close collaboration with municipal health services, health care providers, and the media.